Why exporters can be financially constrained in a recently liberalised economy? A puzzle based on Argentinean firms during the 1990s - Paula Espanol (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
Trade-related characteristics have only been recently started to be included in empirical studies analysing the determinants of the financial constraints faced by firms. A result broadly shared by these studies is that exporting firms tend to be those less financially constrained. In this paper we test this result using panel data built up from quarterly balance sheet information for 74 Argentinean big firms covering the years of the currency board regime (1992-2001). We estimate an investment equation splitting up the sample between exporters and non-exporters. Using three alternative econometric models (random effects, fixed effects and instrumental variables) we find that, contrary to what is commonly stressed in the literature, exporting firms are the ones facing larger financial constraints on investment. We propose an explanation for this original result based on the currency appreciation that follows financial liberalisation processes in emerging countries, particularly in Argentina, which triggers a profit squeeze phenomenon for exportable firms, reducing their investment capacity.
Keywords: O16; E22; O54; 330; financial constraint; investment; foreign trade; Argentine